Problem Based Learning: Upaya Strategis Peningkatan Hasil Belajar Siswa Kelas III Dalam Pembelajaran PKn Materi Kewajiban di Rumah - Mohammad Ilham Saputro; Wahyu Prihanta; Sucipto (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
This study aims to determine the application of the Problem-Based Learning model in improving the learning outcomes of Pancasila Education on obligations at home in grade 3 This study aims to determine the application of the Problem-Based Learning model in improving the learning outcomes of Pancasila Education on obligations at home in grade 3 students at SDN Junrejo 2 Kota Batu in the 2022/2023 Academic Year. Based on the observations, it is known that students have not shown an increase in learning outcomes in the subject matter of obligations at home. The teacher has made efforts to use the lecture method and media around the student's environment. Therefore, we need a learning model that attracts students' attention through real problems in the surrounding environment. This study used data collection techniques in the form of test results, observations, and documentation carried out on 3B class students with 20 research subjects. This Research Problem-Based Learning model is applied to the Pancasila Education module with a time allocation of 4 x 35 minutes through 2 cycles. The results of the research on the application of the Problem-Based Learning model show that there was a positive response by students in learning activities of 91.67% with the achievement of the implementation of the Problem-Based Learning model by the teacher of 97.20% while the learning outcomes of class 3 students experienced an increase in classical achievement by 40% in cycle I and 80% in cycle II. In addition, the Problem-Based Learning model also provides students with the ability to find knowledge.